Creation of Ready to Wear Deluxe with Manipulating Fabric Slashing Inspired by the Golden Sunrise of Bromo - Kusuma, Karina Septia; Nahari, Inty; Kharnolis, Mein; Arifiana, Deny (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
The creation of this work is based on a type of practice-led research approach carried out through a fashion design practice studio with a focus on "Penciptaan Raedy to Wear Deluxe dengan Manipulating Fabric Slashing Terinspirasi dari Golden Sunrise of Bromo". This creative practice study aims to convey the creativity of fashion design which can increase the repertoire of forms and types of clothing that are different from previously existing clothing. This work was inspired by the golden sunrise of Bromo which has its own uniqueness in terms of beautiful and unique visuals and is still very minimally applied or realized as an inspiration for the concept of work by a previous designer. To achieve this goal, the method used in making this work goes through four stages, namely: pre-design, design, embodiment, and presentation by applying the technique of manipulating fabric slashing to the clothing so that it can add creative and aesthetic value to the clothing. The results of this creation process were 2 ready to wear deluxe works which were presented in the form of a fashion show at the 34th Annual UNESA Fashion Show "BHUMIBRAMA" using an outdoor on the floor fashion show presentation technique.